Collocated interaction: new challenges in ‘same time, same place’ research - Fischer, Joel E.; Porcheron, Martin; Lucero, Andrés; Quigley, Aaron; Scott, Stacey D.; Ciolfi, Luigina; Rooksby, John; Memarovic, Nemanja (2016)
In the 25 years since Ellis, Gibbs, and Rein proposed the time-space taxonomy, research in the ‘same time, same place’ quadrant has diversified, perhaps even fragmented. This one-day workshop will bring together researchers with diverse, yet convergent interests in tabletop, surface, mobile, and wearable technologies, spaces and spatial interaction, and those interested in the social aspects of interaction, such as conversation analysis and ethnomethodology. These communities have matured considerably, and produced significant exemplars of systems, methods, and studies concerned with collocated interactions. Yet, new challenges abound as people wear and carry more devices than ever, creating fragmented device ecologies at work, and changing the ways we socialise with each other. In this workshop we seek to start a dialogue to look back as well as forward, review best practices, discuss and design paper-prototypes using the collocated design framework, to consider how we might address new and future challenges through collocated design practice.